Student Well-being: A Systematic Literature Review - Farah Aulia; Thomas Dicky Hastjarjo; Diana Setiyawati; Bhina Patria (Faculty of Psychology Universitas Gadjah Mada, 2020)
Research on well-being in adults has developed quite rapidly in recent years, but not on research in child well-being particularly within school context. This article aimed to review: (a) the definition of student well-being and b) measurement of student well-being. The review involved articles published in 2007-2017. The conclusions of this literature review are (a) the definitions used to explain student well-being are based on several approaches, namely mental health, hedonistic and eudaimonic, (b) several aspects that construct the student well-being at school namely dominant positive emotions, school satisfaction, negative emotions, social relations and engagement to school. These findings can provide recommendations for measurement construction and school evaluation related to student well-being.